Evaluation of root surface roughness produced by hand instruments and ultrasonic scalers: An in vivo study - Farzane Vaziri; Fahimeh Rashidi Maybodi; Mohammad Arab Farashahi (Journal of Advanced Periodontology and Implant Dentistry)
Background. The aim of periodontal treatment is to remove bacterial plaque and dental calculus by hand and power-driven instruments. However, the comparison of the effectiveness of these instruments has always been controversial. Therefore, this in vivo study investigated and compared the effects of hand and ultrasonic piezoelectric instruments on the roughness of dental surfaces under an atomic force microscope (AFM). Methods. In this study, 35 periodontally hopeless teeth were selected and randomly divided into four groups (n=7). The control group consisted of teeth that had to be extracted for orthodontic or prosthetic treatment (n=7). In group one, scaling and root planing were performed using hand instruments. In other groups, scaling and root planing were performed using piezoelectric ultrasonic instruments with low to high power, respectively. Then the scaled teeth were extracted for analysis under an atomic force microscope. Results. This study showed that root roughness significantly differed between different experimental groups (P<0.027). The root roughness (Rq) in the SRP2 group significantly differed from the control group (P<0.05), while no significant differences were observed between the other groups. Furthermore, the least roughness was observed in the SRP3 group, with the highest roughness in the SRP2 group. Conclusion. Within the limitation of this study, there were no significant differences in surface roughness between different powers of the ultrasonic device.